A new modeling approach allowing prediction and comparison of the long-term outcomes of treatments for hemophilia B. (January 2018) - Keep, Marjolijn van; Hoxer, Christina Stentoft; Hemstock, Matthew; Groth, Andreas Velsing; Knight, Christopher
Aim: To develop a modeling approach to compare clinical outcomes of nonacog beta pegol to a standard-acting factor IX (FIX) product.Methods: Regression analysis linked FIX activity to bleed rates. Pharmacokinetic parameters were used to estimate FIX activity over time. The probability of bleeds was estimated for both treatment arms. A Markov model estimated the presence of target joints and annualized bleed rates (ABRs).Results: Higher FIX activity showed reduced ABRs (p < 0.001). Target joints resulted in higher bleed rates (p < 0.001). When FIX activity levels and bleed risks were applied to the Markov model, ABRs for nonacog beta pegol and its comparator were 2.40 and 6.36, respectively.Conclusion: This model provides a starting point for assessing the added value of new FIX products.